Freedom of Religion under Bills of Rights - Babie, Paul; Rochow, Neville (University of Adelaide Press, 2012)
Chapter 1 Paul Babie and Neville Rochow, Protecting Religious Freedom under Bills of Rights: Australia as Microcosm Chapter 2 Ngaire Naffine, How Religion Constrains Law and the Idea of Choice Chapter 3 Bruce Kaye, Is the Emperor Wearing the Wrong Clothes? Human Rights and Social Good in the Context of Australian Secularity: Theological Perspectives Chapter 4 Alan Cadwallader, Anniversary overlap: or what happens when St Paul meets the Universal Declaration of Human Rights Chapter 5 Neil Foster, Defamation and Vilification: Rights to Reputation, Free Speech and Freedom of Religion at Common Law and under Human Rights Laws Chapter 6 Robert C Blitt, Should an Australian Bill of Rights Address Emerging International Human Rights Norms? The Challenge of 'Defamation of Religion' Chapter 7, Patrick Parkinson, Christian Concerns About an Australian Charter of Rights Chapter 8 Asmi Wood, Apostasy in Islam and the Freedom of Religion in International Law Chapter 9 David M Kirkham, Political Culture and Freedom of Conscience: A Case Study of Austria Chapter 10, Cornelia Koch, The Sky is Falling if Judges Decide Religious Controversies! - Or is it? The German Experience of Religious Freedom Under a Bill of Rights Chapter 11 Nicky Jones, Religious Freedom in a Secular Society: The Case of the Islamic Headscarf in France Chapter 12 Ian Leigh, Religious Freedom in the UK After the Human Rights Act 1998 Chapter 13 Frank S Ravitch, Judicial Interpretation, Neutrality and the US Bill of Rights Chapter 14 Brett G Scharffs, Protecting Religious Freedom: Two Counterintuitive Dialectics In US Free Exercise Jurisprudence Chapter 15 Barbara Billingsley, Walking the Tightrope: The Struggle of Canadian Courts to Define Freedom of Religion Under the Canadian Charter of Rights and Freedoms Chapter 16 Charles J Russo, Quo Vadis The Free Exercise of Religion? The Diminishment of Student Religious Expression in US Public Schools Chapter 17 Kris Hanna, Freedom From Discrimination on the Basis of Religion Chapter 18 Rex Tauati Ahdar, Ruminations from the Shaky Isles on Religious Freedom in the Bill of Rights Era Chapter 19 Paul Rishworth, Indigenous Peoples and Bills of Rights